TCRcost: a deep learning model utilizing TCR 3D structure for enhanced of TCR–peptide binding - Li, Fan; Qian, Xinyang; Zhu, Xiaoyan; Lai, Xin; Zhang, Xuanping; Wang, Jiayin (Frontiers in Genetics, 2024)
Predicting TCR-peptide binding is a complex and significant computational problem in systems immunology. During the past decade, a series of computational methods have been developed for better predicting TCR-peptide binding from amino acid sequences. However, the performance of sequence-based methods appears to have hit a bottleneck. Considering the 3D structures of TCRpeptide complexes, which provide much more information, could potentially lead to better prediction outcomes. In this study, we developed TCRcost, a deep learning methods, to predict TCR-peptide binding by incorporating 3D structures. TCRcost overcomes two significant challenges: acquiring a sufficient number of high-quality TCR-peptide structures and effectively extracting information from these structures for binding prediction. TCRcost corrects TCR 3D structures generated by protein structure tools, significantly extending the available datasets. The main and side chains of a TCR structure are separately corrected using a long short-term memory (LSTM) model. This approach prevents interference between the chains and accurately extracts interactions among both adjacent and global atoms. A 3D convolutional neural network (CNN) is designed to extract the atomic features relevant to TCR-peptide binding. The spatial features extracted by the 3D CNN are then processed through a fully connected layer to estimate the probability of TCR-peptide binding. Testing results demonstrated that predicting TCR-peptide binding from TCR 3D structures is both efficient and highly accurate with an average accuracy of 0.974 on precise structures. Furthermore, the average accuracy on corrected structures was 0.762, significantly higher than the 0.375 accuracy on uncorrected original structures. Additionally, the average root-mean-square-distance (RMSD) to precise structures was significantly reduced from 12.753 Å with predicted structures to 8.785 Å with corrected structures. Thus, utilizing structural information of TCR-peptide complexes is a promising approach for improving binding prediction accuracy.